Neonatal Ethanol Exposure Causes Behavioral Deficits in Young Mice. (13th February 2018) - Xu, Wenhua; Hawkey, Andrew B.; Li, Hui; Dai, Lu; Brim, Howard H.; Frank, Jacqueline A.; Luo, Jia; Barron, Susan; Chen, Gang
Abstract : Background: Fetal ethanol (EtOH) exposure can damage the developing central nervous system and lead to cognitive and behavioral deficits, known as fetal alcohol spectrum disorders (FASD). EtOH exposure to mouse pups during early neonatal development was used as a model of EtOH exposure that overlaps the human third‐trimester "brain growth spurt"—a model that has been widely used to study FASD in rats. Methods: C57BL/6 male and female mice were exposed to EtOH (4 g/kg/d) on postnatal days (PD) 4 to 10 by oral intubation. Intubated and nontreated controls were also included. Behavioral testing of the offspring, including open field, elevated plus maze, and Morris water maze, was performed on PD 20 to 45. Results: EtOH exposure during PD 4 to 10 resulted in hyperactivity and deficits in learning and memory in young mice with no apparent sex differences. Conclusions: Based on these data, this neonatal intubation mouse model may be useful for future mechanistic and genetic studies of FASD and for screening of novel therapeutic agents. Abstract : Ethanol exposure via oral intubation on postnatal day (PD) 4–10 resulted in hyperactivity in open field test (A) and deficits in learning and memory in Morris water maze test (B) in young mice with no apparent sex differences.